STUDY ON THE HOT CORROSION RESISTANCE OF FE-20NI-14CR-6AL-1,5TI-0,3SI-0,2C ALUMINA FORMING AUSTENITIC STAINLESS STEEL AT TEMPERATURES OF 700, 800, AND 900Â°C - Jeremy Geraldo, Matthew
The use of electricity increases along with the development of technology around the world. Indonesia’s electricity consumption increased by 5.78% from 2020 to 2021 and is predicted to continue to increase in the future. Electric Steam Power Plants (PLTU) contribute to about 50% of all electricity generation in Indonesia. PLTU is a type of power plant that uses hot steam to turn a turbine. The hot steam comes from the process of evaporation of air through a boiler, this plant uses coal or fuel oil to heat the air. In industrial gas turbines, sulfur reacts with NaCl to form Na2SO4 at high temperatures which causes accelerated oxidation or hot corrosion of components. High temperature operations require materials which have a good combination of corrosion resistance, mechanical properties, and microstructural stability. In this study, hot corrosion testing of Fe-20Ni-14Cr-6Al-1,5Ti-0.3Si-0.2C alumina forming austenitic stainless steel alloy was carried out at temperatures of 700, 800, and 900°C for 5, 20, and 50 hours.